Telotristat in the management of Carcinoid diarrhoea – A real world experience of patients from ENETs centre of excellence in Neuroendocrine tumours. Issue 5 (14th September 2021) - Khanna, Amardeep; Cianci, Nicole; Abbas Shah, Husnain; Goel, Ashish; Jebril, Asma; Chauhan, Jessica; Pipe, Michelle; Shetty, Shishir; Weston, Christopher; Venkataraman, Hema; Smith, Stacey; Vickrage, Suzanne; et al.
Abstract: Background and Aims: Diarrhoea is a common and debilitating symptom of Carcinoid syndrome. Effective control of symptoms is achieved with somatostatin analogues (SSAs) and additional loperamide and/or codeine phosphate. Symptom control is lost with time and disease progression. There is, therefore, a strong need for additional and more effective therapies. Telotristat‐ethyl is a peripheral tryptophan‐hydroxylase inhibitor approved for treatment of diarrhoea. Here, we present our experience of Telotristat for treating carcinoid diarrhoea in a large cohort of patients outside of clinical trials. The primary outcome was reduction in stool frequency of >30%, as defined in most studies. Methods: Patients were identified from a prospective database and information collected retrospectively from the hospital's electronic patient records. We included 31 patients (25 males, 6 females; Median age 69 years) on Telotristat and 10 patients on fortnightly high‐dose SSA (6 males, 4 females; Median age 67 years). Results: The mean (range) duration of treatment in telotristat and 2 weekly SSA groups was 258 (15‐479) and 689 (219‐1446) days respectively. Primary endpoint was achieved in 82% (23/28) patients on Telotristat with median percentage reduction in stool frequency of 60% (IQR 50‐69), compared to 28% (2/7) (22 (−30 to 55) %) in the control group. Odds ratio for reduction in stool frequency >30% was −11, (95% CI 1.71‐77.1). Conclusion: This real world experience supports the effectiveness and safety of Telotristat to treat carcinoid diarrhoea not adequately controlled by standard treatment with SSA.